2014
DOI: 10.1002/jbm.b.33310
|View full text |Cite
|
Sign up to set email alerts
|

Tetracycline tethered to titanium inhibits colonization by Gram‐negative bacteria

Abstract: As peri-prosthetic infection is one of the most devastating complications associated with implant placement, we have reasoned that such infection can be largely subverted by development of antibacterial implants. Our previous work demonstrated that covalent coupling of vancomycin to titanium alloy prevented colonization by the gram-positive pathogens, Staphylococcus aureus and Staphylococcus epidermidis. Some orthopaedic devices, including permanent prosthesis anchors, and most dental implants are transcutaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 30 publications
2
25
0
3
Order By: Relevance
“…However, previous studies have demonstrated that the tethered antibiotics such as vancomycin could block osseointegration processes by down-regulating the molecules required for pre-osteoblast recruitment, proliferation, differentiation and maturation [11,12,24]. Thus, given that the antibiotic itself appears to impair the process of osseointegration, development of an antibiotic possessing both antibacterial properties and the ability to promote osteogenic differentiation would be an ideal candidate for the biofunctionalization of the Ti.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, previous studies have demonstrated that the tethered antibiotics such as vancomycin could block osseointegration processes by down-regulating the molecules required for pre-osteoblast recruitment, proliferation, differentiation and maturation [11,12,24]. Thus, given that the antibiotic itself appears to impair the process of osseointegration, development of an antibiotic possessing both antibacterial properties and the ability to promote osteogenic differentiation would be an ideal candidate for the biofunctionalization of the Ti.…”
Section: Introductionmentioning
confidence: 95%
“…Various approaches had been employed in the fabrication of a biofunctional Ti surface, including changes to surface coating or morphology and the use of covalent or controlled-release antibacterial or bioactive agents on the Ti surface [10][11][12]. However, these strategies have thus far been based on a simple design for singlebiofunctionalization of Ti to either confer an antibacterial property or promote osteogenic differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…An interactive implant surface with pH-dependent or infection-dependent antibiotic release might avoid this shortcoming, but has not yet been introduced to dental implant materials research. Antibiotics are capable of reducing bacterial colonization with S. mutans 22,39) S. epidermidis 31) and S.aureus 38) , P. gingivalis, A. actinomycetemcomitans, P. intermedia, P. aeruginosa 40) and E. coli 21,23,36) on titanium surfaces. Chlorhexidine (CHX)-loaded titanium surfaces reduce colonization with streptococci and S. aureus in comparison to titanium control [24][25][26] .…”
Section: Drug-loaded Surfacesmentioning
confidence: 99%
“…The results showed enhanced alkaline phosphatase activity and calcium deposition by osteoblast cells 27) . Antibiotic-releasing surfaces were non-toxic to osteoblast cells and showed good cytocompatibility compared to uncoated titanium 21,31,36) . Load concentrations of 1.4 and 0.7% CHX resulted in harmful changes in eukaryotic cell morphology, including shrinkage, smaller and pyknotic cells, and loss of cytoplasmic processes, which suggests that there are cytotoxic effects.…”
Section: Drug-loaded Surfacesmentioning
confidence: 99%
“…Various solutions have been recently proposed to improve antibacterial properties of titanium implants: embedment of Ag nanoparticles, ion implantation of Ag, Cu, Zn ions, silver doped hydroxyapatite coatings, covalent coupling of antibiotics such as tetracyclin and vancomycin, ZnO coatings, immobilization of anhydride‐functional silane, chitosan/cefepime nanofiber coatings, etc. Here we discuss two strategies: (1) release of biocide agent; (2) formation of stimuli responsive coating to “push” bacteria “off” the surface.…”
Section: Polyelectrolyte Layer‐by‐layer (Lbl) Assembly For Bio‐experimentioning
confidence: 99%